Peningkatan Hasil Belajar Luas Trapesium dan Layang-layang dengan Pendekatan Contextual Teaching and Learning di Kelas V SD - Atikah Nur; Ritawati Mahyuddin; Masnila Devi (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of the research was to describe an increase the student’s learning achievement on the broad trapezoid and kite in Elementary School by using CTL approach. The research subjects were teachers and fifth grade students of SDN 16 Padangkudo with 24 students consisting of 9 men and 25 women. The instruments used in this study were observation sheets and test sheets in the form of questions. The data analysis technique used is interactive analysis. The results showed an increase from cycle 1 to cycle 2. The results of the Cycle I RPP assessment average was 86.58% (good) and cycle II 92.85% (very good). The results of observations of teacher activities in the first cycle were 87.49% (good) and cycle II 96.42% (very good). Observation of the activities of students in the first cycle averages 78.57% (enough) and the second cycle 89.285. The percentage of learning outcomes in the first cycle averaged 77.92% (enough) and the second cycle 89.67% (good). It can be concluded that, the CTL approach can improve the learning outcomes of trapezoidal and kite class V students in SD N 16 Padangkudo Keyword  : Learning Achievement on the broad trapezoid and kite, CTL apporoach